ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERBANKAN - Yuni Shara (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2019)
This study aims to determine and analyze the influence of BOPO, NPL and institutional ownership on ROA in public banks listed on the Indonesia Stock Exchange. This type of research is causal and the object of this research is all commercial banks listed on the Indonesia Stock Exchange. The data used is secondary data obtained from the Indonesia Stock Exchange for the period 2013-2017. By using a quantitative approach and data analysis using a simple regression analysis model. The results of the study simultaneously the influence of BOPO, NPL and Instutional Ownership have a significant effect on ROA. Partially, BOPO, NPL has a positive and not significant effect on ROA; Instutional ownership has a negative and not significant effect on ROA. Keywords:ROA, BOPO, NPL and Instutional Ownership.